Analisis Persediaan Pangan Beras pada Perusahaan Umum BULOG Kantor Wilayah Bali - ADITYA, I GEDE PUTU DHARMA; USTRIYANA, I NYOMAN GEDE; SURYAWARDANI, I GUSTI AYU OKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022, 2022)
Analysis of Rice Supplies in Perusahaan Umum BULOG Kantor Wilayah Bali Perum BULOG Kanwil Bali is a logistics company that has job manage supply, distribution and price oversee of rice commodity in Bali Province. The research objectives are rice procurement flow, analyse the rice supply system focused on economic orders, safety stock, maximum inventory, reorder point determination, and analyse the cost efficiency of rice supplies in Perum BULOG Kanwil Bali focused data in 2020. This research uses a purposive method with primary data through interviews with key informants and secondary data in the form of library research and documentation. Types of data are rice procurement flow data, rice demand data, rice prices, ordering costs, carrying costs, and lead times. The economic order quantity method is used to analyse rice management by the company. The results of the study indicate 1) Rice procurement flow begins with an order from head office to procure in kanwil, contract negotiation with partners, publishing document ordered, next to rice distribution and document-quality survey checking at the destination warehouse; 2) An economic orders is 614,436 tons or about 31 times a year, the amount of safety stock should be 4,815,370 tons with 5.429,806 tons of maximum inventory and the reorder point of inventory level ought to 5,184,768 tons; 3) Cost efficiency obtained by Perum Bulog Kanwil Bali by using the EOQ method is about Rp. 81.200.288,793.